Detection of movement-related cortical potentials based on subject-independent training - Niazi, Imran Khan; Jiang, Ning; Jochumsen, Mads; Nielsen, Jorgen Feldbaek; Dremstrup, Kim; Farina, Dario (Springer Verlag, 2013)
To allow a routinely use of brain-computer interfaces (BCI), there is a need to reduce or completely eliminate the time-consuming part of the individualized training of the user. In this study, we investigate the possibility of avoiding the individual training phase in the detection of movement intention in asynchronous BCIs based on movement-related cortical potential (MRCP). EEG signals were recorded during ballistic ankle dorsiflexions executed (ME) or imagined (MI) by 20 healthy subjects, and attempted by five stroke subjects. These recordings were used to identify a template (as average over all subjects) for the initial negative phase of the MRCPs, after the application of an optimized spatial filtering used for pre-processing. Using this template, the detection accuracy (mean +/- A SD) calculated as true positive rate (estimated with leave-one-out procedure) for ME was 69 +/- A 21 and 58 +/- A 11 % on single trial basis for healthy and stroke subjects, respectively. This performance was similar to that obtained using an individual template for each subject, which led to accuracies of 71 +/- A 6 and 55 +/- A 12 % for healthy and stroke subjects, respectively. The detection accuracy for the MI data was 65 +/- A 22 % with the average template and 60 +/- A 13 % with the individual template. These results indicate the possibility of detecting movement intention without an individual training phase and without a significant loss in performance.
Keywords: EEG signal processing; Movement-related cortical potential; Stroke rehabilitation; Motor imaginary; Subject training